Transforaminal Lumbar Endoscopic Discectomy: A Novel Alternative for Management of Lumbar Disc Herniation in Patients With Rheumatoid Arthritis? - Stylianos Kapetanakis; Constantinos Chaniotakis; Paschalis Tsioulas; Nikolaos Gkantsinikoudis (Neurospine)
Objective Lumbar disc herniation (LDH) represents an increasingly encountered condition in patients with rheumatoid arthritis (RA). The aim of the present study is to assess the progress of health-related quality of life following transforaminal endoscopic lumbar discectomy (TELD) for LDH in patients suffering from RA. Methods Seventy-four patients, scheduled to undergo elective TELD for LDH, were prospectively enrolled in the study. Group A included 36 otherwise healthy individuals and group B 38 patients complementarily diagnosed with RA according to the 2010 ACR/EULAR (American College of Rheumatology/European League Against Rheumatism) criteria. The Medical Outcomes Study 36-item Short Form health survey (SF-36) was selected for the outcome assessment at baseline and postoperatively, at selected intervals at 6 weeks, 3, 6, and 12 months postoperatively. Results Group A presented statistically significantly higher scores in all SF-36 domains and all selected intervals (p<0.001), except for mental health parameter. All aspects of SF-36 questionnaire significantly improved postoperatively (p<0.001) and in each group independently. Nevertheless, the absolute improvement between consecutive time intervals did not differ significantly between the 2 groups. Conclusion Patients diagnosed with RA who undergo TELD for LDH demonstrate statistically significant improvement in their health status, as measured by SF-36 questionnaire, one year after the procedure. This improvement is comparable with normal individuals.